GIS Based Flood Vulnerability Mapping in the Batang Kuranji Watershed, Padang City due to Land Conversion - Fauzan Muhammad; Aaron Kristian; Ratna Wilis; Triyatno; Cahyadi Nugroho; L Sukardi (Sumatra Journal of Disaster, Geography and Geography Education, 2026)
Flood is one of the most frequent hydrometeorological disasters in Padang City, closely related to land use change and the degradation of watershed functions. Rapid urban development in the Batang Kuranji Watershed has led to the expansion of built-up areas, which reduces land infiltration capacity and increases surface runoff, thereby intensifying flood risk, especially in downstream areas. The advancement of remote sensing technology and Geographic Information Systems (GIS) enables comprehensive spatial analysis to assess land use dynamics and flood hazard distribution at the watershed scale. This study aims to analyze land use changes in Padang City during the 2017–2025 period and to identify flood hazard and vulnerability levels in the Batang Kuranji Watershed based on multiple physical and hydrometeorological parameters. The analysis utilizes Landsat 8 imagery, CHIRPS rainfall data, DEMNAS-derived slope data, soil type information, river buffer analysis, and spatial planning data, which are processed using scoring and overlay methods within a GIS environment. The results indicate a continuous increase in built-up areas accompanied by a reduction in agricultural land and natural vegetation, particularly in the middle to downstream sections of the watershed. Flood hazard analysis shows that most of the watershed area falls into the low to moderate hazard classes; however, areas categorized as high hazard are concentrated in lowland regions and river corridors with dense settlements. These critical zones have limited water absorption capacity and are highly susceptible to flooding and inundation during periods of high rainfall. Therefore, spatial monitoring of land use change and flood hazard distribution is essential as part of an integrated flood mitigation strategy to support sustainable watershed management and spatial planning in Padang City.